The psychology of religion : an empirical approach - Spilka, Bernard, 1926- (New York ; London : Guilford Press, 2003)
"The authors synthesize classic and contemporary research on religious thought, belief, and behavior across the lifespan; the forms and meaning of religious experience; the social psychology of religious organizations; and connections to biology, morality, coping, and mental health. As in previous editions, the focus is on scientific work that is moving the psychology of religion into the mainstream of academic psychology, rather than broad interpretative and conceptual discussions. Organized for optimal use in advanced undergraduate- or graduate-level courses, every chapter features thought-provoking quotations, sidebars, and examples that bring key concepts to life."--BOOK JACKET.
Publisher description: Now in a fully revised and expanded third edition, this landmark text provides comprehensive, up-to-date coverage of an increasingly rich and varied field. The authors synthesize classic and contemporary research on religious thought, belief, and behavior across the lifespan the forms and meaning of religious experience the social psychology of religious organizations and connections to biology, morality, coping, and mental health. As in previous editions, the focus is on scientific work that is moving the psychology of religion into the mainstream of academic psychology, rather than broad interpretative and conceptual discussions. Organized for optimal use in advanced undergraduate- or graduate-level courses, every chapter features thought-provoking quotations, sidebars, and examples that bring key concepts to life.
The psychological nature and functions of religion -- Foundations for an empirical psychology of religion -- Religion and biology -- Religion in childhood -- Religious socialization and thought in adolescence and young adulthood -- The form and content of adult religion -- The roles and functions of religion in adult life -- Religion and death -- Religious experience -- Mysticism -- Conversion -- The social psychology of religious organizations -- Religion and morality -- Helping behavior and prejudice -- Religion, coping, and adjustment -- Religion and mental disorder -- Epilogue.
Previous edition entered under: Spilks, Bernard.
Includes bibliographical references (p. 545-639) and indexes.
Keywords: Psychology, Religious